Veracissima Enim Sunt Angelica Et Prophetica Oracula - Rose, Paula (2018)
This contribution explores the interface between pagan divination and scriptural prophecy in Augustine's works. Both angels and demons function as intermediaries between humans and the divine realm, which makes it possible to interpret one prediction in various ways, either as an authentic scriptural prophecy or as a foretelling inspired by demons. A close reading of Augustine's treatise De diuinatione daemonum and De ciuitate Dei 7,34/5 forms the theoretical frame of this paper which discusses one example of a divination narrative in three works by Augustine. The story of the medium in Endor who predicts King Saul's death is mentioned in De doctrina christiana, Epistula 43 and De cura pro mortuis gerenda. A comparison of these three references shows that Augustine uses the versatility of this divination/prophecy narrative. He seems to emphasize different aspects of the narrative as the communicative purpose of the specific text requires. The picture that emerges from Augustine's works is not that of a clear transformation of pagan divination into scriptural prophecy, but that of effective rhetorical use of the versatility of a given narrative.
Keywords: Angels; AUGUSTINE, Saint, Bishop of Hippo, 354-430; Demonology; Divination; Forecasting; Human Beings; Narratives; Paul, The Apostle, Saint; Prophecy